The Development of E-Learning Based Schoology of Learning Media about Animalia Material for 10th Grade High School - M Risai Yoanda; Rahmadhani Fitri; Ristiono Ristiono; Ramadhan Sumarmin (ATRIUM PENDIDIKAN BIOLOGI, 2019)
Teaching and learning process is an interaction between the teacher and students that takes place in learning to achieve learning objectives.Teachers have limitations in teaching students, although there are still many positive things that can be obtained from it, some of the limitations are one of them, students who are less motivated to bring thick books due to weight and so on, in the learning process of Information Communication Technology (ICT) where the use of technology can be implemented in the collection of files and books that can be stored in e-learning media so that students do not need to carry thick and heavy books. Then the schoology-based e-learning learning media was developed for 10th grade high school students. This media development uses three stages of 4-D models. The object of this research is the learning media of barbarian schoology e-learning for 10th grade students. The media schoology was validated by 2 Biology Department lecturers from the Faculty of Mathematics and Natural Sciences and 1 Pariaman High School teacher, it was conducted to determine the practicality level of schoology media by the teacher and 10th grade students of Pariaman 1 High School. This research produces schoology-based e-learning media learning products about animalia material for grade X high school / MA students with very valid criteria for validity testing, and very practical criteria for practicality tests for teachers and students. So it can be concluded that the school-based e-learning learning media developed are valid and practical to use.